Organopolysiloxane composition, preparation method, chip mounting material and optical semiconductor device

By using modified and unmodified alumina compounding technology in thermally-conductive crystal glue, the contradiction between thermal conductivity and bonding properties is solved, and an organopolysiloxane composition with high thermal conductivity and high adhesion is achieved, which improves the thermal management and reliability of LED chip mounting materials.

CN119899629APending Publication Date: 2025-04-29QINGYUAN HUMAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411872301.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

While improving thermal conductivity, the existing thermally conductive crystal glue affects the bonding performance of the colloid, and there is a gap between the thermally conductive fillers, resulting in poor thermal conductivity.

Method used

The organic polysiloxane composition is adopted, including the composite of modified alumina and unmodified alumina. The modified alumina is modified by a silane coupling agent to reduce the bonding point of hydrogen bonds and improve thermal conductivity; the unmodified alumina is formed by hydrogen bonding to improve the bonding performance.

Benefits of technology

Without affecting the viscosity of the colloid, the addition of thermal filler is improved, the colloid is achieved with excellent thermal conductivity and high adhesion, and the thermal management and reliability of LED chip mounting materials are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899629A_ABST
    Figure CN119899629A_ABST
Patent Text Reader

Abstract

The invention provides an organopolysiloxane composition, a preparation method, a chip mounting material and an optical semiconductor device in order to solve the problem that the adhesive property of colloid is influenced while the heat-conducting property of the organopolysiloxane composition is improved in the prior art. The organopolysiloxane composition comprises organic hydrogen polysiloxane, alkenyl-containing organopolysiloxane and a heat-conducting filler, the heat-conducting filler comprises modified aluminum oxide and unmodified aluminum oxide, and the modified aluminum oxide is modified by a silane coupling agent; the compounding mass ratio of the modified aluminum oxide to the unmodified aluminum oxide is 0.2-5. According to the organopolysiloxane composition provided by the invention, the modified aluminum oxide and the unmodified aluminum oxide are compounded to prepare the organopolysiloxane composition, the high heat-conducting property and the high adhesive force of the organopolysiloxane composition are met at the same time, and in addition, when the compounding mass ratio of the modified aluminum oxide and the unmodified aluminum oxide meets the limiting range of 0.2-5, the adhesive force of the organopolysiloxane composition can be improved. The heat-conducting property and the adhesive force of the organopolysiloxane composition can be further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic adhesives, and in particular relates to an organic polysiloxane composition, a preparation method, a chip mounting material and an optical semiconductor device. Background Art

[0002] For low-power LEDs, the heat generated is very small, and basically no heat dissipation measures are needed to achieve good application. However, for high-power LED devices used in lighting fields such as commercial buildings, roads, tunnels, and industrial and mining industries, if 75% of the input power cannot be converted into heat energy in time, the heat accumulation will cause the chip temperature to rise rapidly, thereby exacerbating the aging, attenuation, and color shift of the device. At the same time, thermal stress will be generated in the LED package, causing a series of reliability problems. As LEDs develop towards high light intensity and high power, the package structure becomes more and more complex, the volume becomes smaller, and the power density becomes larger. The heat dissipation problem becomes more prominent, which has become a key problem that must be solved in LED packaging. As the bonding material between the chip and the bracket, the chip bonding material is the first link in the transfer of heat energy. Its mechanical strength, bonding strength, heat resistance, and thermal conductivity directly determine the failure rate, attenuation rate, and reliability of the LED device, and it occupies an important position in the entire LED thermal topology. Therefore, the development of chip bonding materials with high reliability is of great significance to promote the rapid development of the LED industry and promote and popularize LED commercial lighting.

[0003] The preparation method of thermal conductive bonding material is generally to directly mix it with resin, cross-linking agent, catalyst, adhesive, etc., and disperse it evenly under a high-speed stirring process. The insulating bonding glue made in this way has evenly dispersed internal thermal conductive fillers, but under the microscopic state, there are still gaps between the thermal conductive fillers, which are filled with resin matrix, and the heat conduction efficiency is poor.

[0004] When the distance between fillers is shortened by increasing the amount of thermal conductive filler to improve the thermal conductivity, the colloid viscosity and bonding properties will restrict the amount of thermal conductive filler added. Therefore, the maximum thermal conductivity of the existing thermal conductive die-bonding adhesive is only 1W / k, and due to the high amount of thermal conductive powder added, more solvents are needed to reduce the viscosity. Summary of the invention

[0005] Aiming at the problem in the prior art that the bonding performance of the colloid is affected while the thermal conductivity of the die-bonding adhesive is improved, an organic polysiloxane composition, a preparation method, a chip mounting material and an optical semiconductor device are provided.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides an organopolysiloxane composition, comprising an organohydrogenpolysiloxane, an organopolysiloxane containing an alkenyl group, and a thermally conductive filler, wherein the thermally conductive filler comprises modified alumina and unmodified alumina, wherein the modified alumina is modified by a silane coupling agent, and the unmodified alumina is not modified by a silane coupling agent; The composite mass ratio of the modified alumina to the unmodified alumina is 0.2-5. Optionally, the particle size D50 of the modified alumina is 2-5 μm, and the particle size D50 of the unmodified alumina is 0.5-1 μm.

[0007] Optionally, the modified alumina has a spherical structure, and the unmodified alumina has an elliptical structure.

[0008] Optionally, the thermally conductive filler includes the following parts by weight: 30~600 parts of modified alumina; 30~600 parts of unmodified alumina.

[0009] Optionally, the organopolysiloxane composition further comprises the following components in parts by weight: 100 parts of organopolysiloxane containing alkenyl groups; 10~60 parts of toughening diluent; 20-40 parts of organohydrogenpolysiloxane; 1~15 parts of tackifier; Inhibitor 0.01~5 parts; 5~30 parts of diluent.

[0010] Optionally, a catalyst is also included, and the catalyst is a platinum group metal catalyst, and the content of the platinum group metal catalyst is 0.01 to 1000 ppm relative to the mass of the organopolysiloxane resin, calculated as the mass of the platinum group metal.

[0011] Optionally, the alkenyl-containing organopolysiloxane is a vinyl VMQ type resin having a vinyl content of 0.05 to 1.1 mol / 100 g.

[0012] Optionally, the toughening diluent is a VMD structured vinyl-terminated silicone oil, and the viscosity of the toughening diluent is 50-500cp; The tackifier comprises an organic silicon polymer containing epoxy, vinyl and methoxy groups, the content of vinyl in the tackifier is 0.05-1 mol / 100g, and the equivalent of epoxy in the tackifier is 200-600.

[0013] Optionally, the organohydrogenpolysiloxane includes one or more hydrogen-containing compounds of HMQ and HMD structures; The viscosity of the organohydrogenpolysiloxane is 1-50 cp, and the hydrogen content of the organohydrogenpolysiloxane is 0.6-2 mol / 100g.

[0014] In another aspect, the present invention provides a method for preparing an organopolysiloxane composition, comprising the following steps: The alkenyl-containing organopolysiloxane, toughening diluent and inhibitor are uniformly mixed to obtain a resin solution; Add the thermal conductive filler to the resin solution and mix evenly to obtain a base colloid; Taking a tackifier and an organohydrogen polysiloxane and mixing them evenly to obtain a preformed colloid; The catalyst is added to the prefabricated colloid, and the organic polysiloxane composition is obtained after mixing and degassing.

[0015] In another aspect, the present invention provides a chip attach material, comprising the organopolysiloxane composition.

[0016] In another aspect, the present invention provides an optical semiconductor device comprising the die attach material.

[0017] The beneficial effects of the present invention are: The organopolysiloxane composition provided by the present invention comprises organohydrogenpolysiloxane, organopolysiloxane containing alkenyl groups and thermally conductive filler, wherein the thermally conductive filler comprises modified alumina and unmodified alumina, and the modified alumina and unmodified alumina of the thermally conductive filler are used together, and the surface hydroxyl groups of the modified alumina are reduced after being modified by a silane coupling agent, thereby reducing the bonding points of hydrogen bonds, and having a small effect on the thixotropy of the organopolysiloxane composition, thereby reducing the viscosity of the system, and at the same time, the modified alumina also promotes the compatibility of the powder in the colloid in the composition with other systems in the colloid, and can increase the addition amount of the thermally conductive filler without affecting the viscosity of the colloid, so as to achieve excellent thermal conductivity of the colloid. On the other hand, the unmodified alumina added in the present application contains a large number of hydroxyl groups on its surface, which has a significant thickening effect, thereby exerting a strong adhesion, improving the bonding performance of the colloid in the composition, and the spatial network structure formed by hydrogen bonds is more stable, and the thixotropic performance is more superior; when the composite mass ratio of the modified alumina and the unmodified alumina meets the restriction range of 0.2 to 5 of the present application, the thermal conductivity and adhesion of the prepared organopolysiloxane composition can be further promoted; in summary, the operation of preparing the organopolysiloxane composition by composite modified alumina and unmodified alumina in the present application can take into account both the high thermal conductivity and high adhesion of the colloid in the composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a preparation flow chart of the organopolysiloxane composition provided by the present invention. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] The present invention provides an organopolysiloxane composition, comprising an organohydrogenpolysiloxane, an organopolysiloxane containing an alkenyl group and a thermally conductive filler, wherein the thermally conductive filler comprises modified alumina and unmodified alumina, wherein the modified alumina is modified by a silane coupling agent, and the unmodified alumina is not modified by a silane coupling agent; The composite mass ratio of the modified alumina to the alumina is 0.2-5.

[0021] Specifically, the organopolysiloxane composition provided by the present invention comprises an organohydrogenpolysiloxane, an organopolysiloxane containing an alkenyl group and a thermally conductive filler, wherein the thermally conductive filler comprises modified alumina and unmodified alumina, and the modified alumina and unmodified alumina of the thermally conductive filler are used together, and the surface hydroxyl groups of the modified alumina are reduced after being modified by a silane coupling agent, thereby reducing the bonding points of hydrogen bonds, and having a small effect on the thixotropy of the organopolysiloxane composition and reducing the viscosity of the system. At the same time, the modified alumina also promotes the compatibility of the powder in the colloid in the composition with other systems in the colloid, and the addition amount of the thermally conductive filler can be increased without affecting the viscosity of the colloid, so as to achieve excellent thermal conductivity of the colloid. Thermal properties; on the other hand, the unmodified alumina added in the present application contains a large number of hydroxyl groups on its surface, and has a significant thickening effect, thereby exerting a strong adhesion, improving the bonding properties of the colloid in the composition, and the spatial network structure formed by hydrogen bonds is more stable, and the thixotropic properties exhibited are more superior; when the composite mass ratio of the modified alumina and the unmodified alumina meets the restriction range of 0.2 to 5 of the present application, the thermal conductivity and adhesion of the prepared organopolysiloxane composition can be further promoted; in summary, the operation of preparing the organopolysiloxane composition by composite of modified alumina and unmodified alumina in the present application can take into account both the high thermal conductivity and high adhesion of the colloid in the composition.

[0022] Specifically, the mass ratio of the modified alumina to the unmodified alumina can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 4 or 5. In a preferred embodiment, the mass ratio of the modified alumina to the unmodified alumina is 0.5. By optimizing the mass ratio of the modified alumina to the unmodified alumina, it is possible to ensure that there are sufficient hydroxyl groups to provide hydrogen bonding points and retain the excellent thixotropy of the organopolysiloxane composition. At the same time, the modified alumina with low hydrogen bonding force and the unmodified alumina with high hydrogen bonding force are filled in the organopolysiloxane composition after optimized configuration, which is more conducive to maintaining the long-term stability of the organopolysiloxane composition and ensuring that the bonding performance is improved under the premise of suitable thixotropic properties.

[0023] The ultimate purpose of the above-mentioned modified alumina modification method is to improve the dispersibility and compatibility of alumina and enhance its application performance as a filler.

[0024] In some embodiments, the particle size D50 of the modified alumina is 2-5 μm, and the particle size D50 of the unmodified alumina is 0.5-1 μm.

[0025] Specifically, the particle size D50 of the modified alumina may be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, and the particle size D50 of the unmodified alumina may be 0.5 μm, 0.7 μm or 1 μm; In some embodiments, the modified alumina has a spherical structure, and the unmodified alumina has an elliptical structure.

[0026] Specifically, the modified alumina is spherical or quasi-spherical, and the unmodified alumina may be elliptical. Specifically, due to their highly symmetrical structure, spherical particles are closely arranged in the system medium, reducing the gaps between particles, thereby helping to enhance the viscosity and stability of the system; in the present application, by optimizing the compounding of thermally conductive powders (modified alumina and unmodified alumina) of different particle sizes and morphologies, the particles can be stacked more densely, the gaps between thermally conductive fillers can be reduced, and a tight three-dimensional structure can be formed, which can not only ensure the thermal conductivity of the organopolysiloxane composition, but also form a stable structure between the powders to ensure their adhesion.

[0027] In some embodiments, the thermally conductive filler includes the following parts by weight: 30~600 parts of modified alumina; 30~600 parts of unmodified alumina.

[0028] Specifically, in a preferred embodiment of the present application, the total addition amount of the modified alumina and the unmodified alumina is 400 parts.

[0029] In some embodiments, the organopolysiloxane composition further comprises the following components in parts by weight: 100 parts of organopolysiloxane containing alkenyl groups; 10~60 parts of toughening diluent; 20-40 parts of organohydrogenpolysiloxane; 1~15 parts of tackifier; Inhibitor 0.01~5 parts; 5~30 parts of diluent.

[0030] Specifically, the alkenyl-containing organopolysiloxane is a main component of the organopolysiloxane composition. During the curing process, the alkenyl-containing organopolysiloxane can form a strong network structure, so that the prepared organopolysiloxane composition has excellent mechanical strength; the toughening diluent plays a role in adjusting the viscosity of the organopolysiloxane composition, ensuring the fluidity and operability of the colloid in the organopolysiloxane composition. An appropriate amount of diluent can help the alkenyl-containing organopolysiloxane to better infiltrate fillers and other additives, thereby improving the uniformity of the mixture; the organohydrogenpolysiloxane is used as a crosslinking agent during the curing process. By reacting with the silanol group of the organopolysiloxane containing alkenyl groups, a more stable siloxy bond is formed, thereby improving the chemical stability and heat resistance of the cured product; the tackifier can significantly improve the adhesion of the organopolysiloxane composition to the substrate. By selecting a suitable tackifier, the compatibility of the colloid with other materials can also be adjusted to ensure good adhesion performance under different environments; the role of the inhibitor is mainly to prevent or delay the progress of the curing reaction, thereby extending the applicability and storage stability of the organopolysiloxane composition. In addition, the inhibitor can also reduce unnecessary side reactions and avoid spontaneous curing problems caused by temperature fluctuations or other changes in conditions.

[0031] In some embodiments, the catalyst is further included, and the catalyst is a platinum group metal catalyst. The content of the platinum group metal catalyst is 0.01 to 1000 ppm relative to the mass of the organopolysiloxane resin in terms of the mass of the platinum group metal.

[0032] Specifically, the type of catalyst described in the present application is not particularly limited, including but not limited to platinum group metals such as platinum, palladium, and rhodium; platinum compounds such as chloroplatinic acid, alcohol-modified chloroplatinic acid, and coordination compounds of chloroplatinic acid with olefins, vinylsiloxanes or acetylene compounds; platinum group metal compounds such as tetrakis(triphenylphosphine)palladium and tris(triphenylphosphine)rhodium chloride.

[0033] In some embodiments, the alkenyl-containing organopolysiloxane is a vinyl VMQ type resin having a vinyl content of 0.05 to 1.1 mol / 100 g.

[0034] Specifically, the vinyl VMQ type resin reacts with the hydrogenated silicone oil crosslinking agent through a hydrosilylation reaction to form a stable siloxane bond, thereby enhancing the three-dimensional network structure of the composition. The crosslinking density can be controlled by adjusting the vinyl content of the alkenyl-containing organopolysiloxane, thereby optimizing the hardness and elasticity of the composition. If the vinyl content in the alkenyl-containing organopolysiloxane is too high, uneven distribution of crosslinking points and stress concentration may result, which is not conducive to improving the mechanical strength and service life of the organopolysiloxane composition.

[0035] In some embodiments, the toughening diluent is a VMD structured vinyl-terminated silicone oil, and the viscosity of the toughening diluent is 50-500 cp.

[0036] Specifically, the VMD structured vinyl-terminated silicone oil is a polydimethylsiloxane having a vinyl terminal group. The viscosity of the toughening diluent determines the fluidity of the VMD silicone oil when preparing the organic polysiloxane composition. In the present application, the viscosity of the toughening diluent is set at 50~500cp, which has good fluidity and can provide better structural strength and stability.

[0037] In some embodiments, the organohydrogenpolysiloxane includes one or more hydrogen-containing compounds of HMQ and HMD structures; The viscosity of the organohydrogenpolysiloxane is 1-50 cp, and the hydrogen content of the organohydrogenpolysiloxane is 0.6-2 mol / 100g.

[0038] It should be noted that the hydrogen content of the organohydrogenpolysiloxane affects the crosslinking density during the preparation of the colloid. When the hydrogen content is high, the Si-H bonds involved in the crosslinking reaction increase, generating a higher density three-dimensional network structure, and improving the mechanical strength, hardness and chemical resistance of the organopolysiloxane composition. However, too high a crosslinking density may cause the material to become brittle and hard, affecting its impact resistance. In addition, the content is closely related to the curing rate. A higher hydrogen content can accelerate the curing reaction and shorten the production cycle, but it may also be difficult to control due to too fast a reaction, resulting in uneven curing or thermal stress concentration.

[0039] Specifically, the present application adjusts the hydrogen content of the organohydrogenpolysiloxane to between 0.6 and 2 mol / 100 g to ensure that the organopolysiloxane composition has excellent mechanical properties and thermal stability.

[0040] Specifically, in a preferred embodiment, the viscosity of the organohydrogenpolysiloxane is controlled to be between 1 and 50 cp to avoid the influence of too low or too high viscosity on the transparency and mechanical properties of the colloid.

[0041] In some embodiments, the tackifier includes an organic silicon polymer containing epoxy, vinyl and methoxy groups, the content of vinyl in the tackifier is 0.05-1 mol / 100 g, and the equivalent of epoxy in the tackifier is 200-600.

[0042] Specifically, epoxy-, vinyl- and methoxy-containing silicone polymers are a class of reactive low molecular weight or prepolymers, which contain epoxy, vinyl and methoxy groups in their molecular structure, and these groups can provide strong adhesion to the colloid in the tackifier; The vinyl content in the tackifier of the present application is 0.05-1 mol / 100 g. The vinyl content within this range can provide good reactivity and crosslinking density. A higher vinyl content can increase the crosslinking degree of the material, thereby enhancing its mechanical strength and heat resistance. The epoxy equivalent of the tackifier of the present application is 200-600. The epoxy equivalent in this range ensures that the tackifier has good reactivity and bonding ability. The epoxy group forms a covalent bond through a ring-opening reaction, which is beneficial to improving the adhesion of the colloid.

[0043] In some embodiments, the inhibitor comprises one or more of acetylenic alcohol compounds, phosphides, and amines.

[0044] Specifically, the acetylene alcohol compound includes one or more of acetylene alcohol, propynylene alcohol and phenylacetylene alcohol; during the preparation process of the organopolysiloxane composition, the inhibitor effectively controls the catalyst reaction rate and time to ensure the operability of the preparation of the organopolysiloxane composition, thereby improving the stability and storage stability of the organopolysiloxane composition.

[0045] Another embodiment of the present invention provides a method for preparing an organopolysiloxane composition, comprising the following operations: The alkenyl-containing organopolysiloxane, toughening diluent and inhibitor are uniformly mixed to obtain a resin solution; Add the thermal conductive filler to the resin solution and mix evenly to obtain a base colloid; Taking a tackifier and an organohydrogen polysiloxane and mixing them evenly to obtain a preformed colloid; The catalyst is added to the prefabricated colloid, and the organic polysiloxane composition is obtained after mixing and degassing.

[0046] Another embodiment of the present invention provides a chip mounting material, comprising the organopolysiloxane composition.

[0047] Another embodiment of the present invention provides an optical semiconductor device, comprising the chip mounting material. The present invention is further described below through embodiments.

[0048] Table 1 Example 1 This example is used to illustrate an organopolysiloxane composition and a preparation method thereof disclosed in the present invention, and includes the following steps: S1: 100 parts of an organopolysiloxane containing an alkenyl group, 22 parts of a toughening diluent and 0.4 parts of an inhibitor are uniformly mixed to obtain a resin solution; S2: Take 200 parts of modified alumina and 200 parts of unmodified alumina and add them to the resin solution, mix them evenly, and obtain a base colloid; S3: taking 5 parts of a tackifier and 33 parts of an organohydrogenpolysiloxane and mixing them evenly to obtain a preformed colloid; S4: 0.4 parts of a catalyst is added to the preformed colloid, and the organic polysiloxane composition is obtained after mixing and degassing.

[0049] Embodiments 2 to 7 This example is used to illustrate an organopolysiloxane composition and a preparation method thereof disclosed in the present invention, and includes most of the operations in Example 1, except that: The amount of each component added to prepare the organopolysiloxane composition shall be based on the corresponding component in Table 1.

[0050] Comparative Examples 1 to 3 This comparative example is used to compare and illustrate an organopolysiloxane composition and a preparation method thereof disclosed in the present invention, and includes most of the operations in Example 1, except that: The amount of each component added to prepare the organopolysiloxane composition shall be based on the corresponding component in Table 1.

[0051] Performance Testing The following performance tests were performed on Examples 1 to 7 and Comparative Examples 1 to 3 prepared as above: 1) Viscosity test: At 25°C, use a Brookfield cap2000+ cone and plate viscometer to test the sample viscosity according to the instructions.

[0052] 2) Thixotropy test: Use a thixotrope tester, select a 25mm parallel plate, and perform a frequency sweep test for 0.01S -1 →100S -1 , calculate the thixotropic index = 1S -1 / 10S -1 .

[0053] 3) Glue throwing test: The equipment used was Xinyichang double-head high-speed die bonding machine GTS100 BH-PA, with a die bonding rate of 50k / h. 10×30mil silicon wafers were bonded to 2835 brackets. Each organopolysiloxane composition was bonded to one bracket (the specification of 2835 brackets was 16×36, with a total of 576 pieces). After the wafers were bonded, the residual glue left on the bracket and the upper part of the chip due to glue throwing was counted under a microscope.

[0054] 4) Thrust test: The bracket with the chip fixed was cured at 170℃ for 2h, and the force value when the chip was pushed away was tested using the force gauge LB-8100A; 5) Use a standard mold to prepare a circular test piece with a thickness of 3-8mm and a diameter of 30mm, which is smooth on both sides. Place it on the DRL-III thermal conductivity meter and test it according to the instrument operating instructions. Set the hot pole temperature to 75℃ and the cold pole temperature to 25℃. Each time the machine is turned on for testing, a standard glass piece sample needs to be tested for calibration to prepare a 10*3.5mm circular piece, and then the thermal conductivity test is performed using a thermal conductivity meter.

[0055] The test results obtained are entered in Table 2.

[0056] Table 2 It can be seen from the test results in Table 2 that the thermal conductivity of Examples 1 to 7 is better than that of Comparative Examples 1 to 3. Among Examples 2 to 4, the overall test effect of Example 4 is better. The compounding mass ratio of the modified alumina to the unmodified alumina in Example 4 is 0.5, the compounding mass ratio of Example 2 is 2, and the compounding mass ratio of Example 3 is 4. It can be seen from the test results of Example 4 that when the mass ratio of the modified alumina to the unmodified alumina is 0.5, the overall performance of the compounded organopolysiloxane composition is better. Among them, the thermal conductivity of Comparative Example 2 is the lowest, because the unmodified aluminum oxide described in the present application is not added in the comparative example, and only adding a single modified aluminum oxide cannot improve or enhance the thermal conductivity of the prepared organopolysiloxane composition; The viscosity of Comparative Example 1 is the highest because a large amount of unmodified alumina is added to Comparative Example 1 compared with other comparative examples and embodiments. The surface of unmodified alumina contains a large amount of hydroxyl groups. When the density of hydroxyl groups on the surface of unmodified alumina is high, more hydrogen bonding sites can be provided, so that it has better adsorption, and the prepared organopolysiloxane composition can be made more viscous. Correspondingly, the thixotropy, the test values ​​of the spinning particles and the chip thrust of Comparative Example 1 are higher; the viscosity of Example 3 and Comparative Example 2 is relatively low because the addition amount of unmodified alumina in Example 3 is relatively low, and no unmodified alumina is added in Comparative Example 2. The test results show that the thixotropy, the spinning particles and the chip thrust values ​​of the two are correspondingly reduced; The particle size of the modified alumina in Example 1 is smaller than that of the modified alumina in Example 6, and the particle size of the unmodified alumina in Example 1 is smaller than that of the unmodified alumina in Example 6. It can be seen from the comparison of the test results of Example 1 with those of Example 6 that the thermal conductivity of Example 1 is slightly higher. The reason is that the difference in size between the modified alumina particle size and the unmodified alumina particle size is relatively large, so the gap between the thermally conductive fillers can be reduced to form a compact three-dimensional structure, thereby ensuring the thermal conductivity of the organopolysiloxane composition. In summary, the organopolysiloxane composition provided by the present invention, on the one hand, uses the modified alumina and unmodified alumina of the thermal conductive filler in combination, and the surface hydroxyl groups of the modified alumina are reduced after the modification treatment, thereby reducing the bonding points of hydrogen bonds, having little effect on the thixotropy of the colloid and reducing the viscosity of the system. At the same time, the modified alumina also promotes the compatibility of the powder in the colloid with other systems in the colloid, and can increase the amount of the thermal conductive filler added without affecting the viscosity of the colloid, so as to achieve the excellent thermal conductivity of the colloid; on the other hand, the unmodified alumina added in the present application contains a large number of hydroxyl groups on its surface, and has a significant thickening effect, thereby exerting a strong adhesion, improving the bonding performance of the colloid, and the spatial network structure formed by hydrogen bonds is more stable, and the thixotropic performance is more superior; secondly, when the compounding ratio of the modified alumina and the unmodified alumina is within the limit of the present application, the thermal conductivity and adhesion of the prepared organopolysiloxane composition can be further promoted.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An organopolysiloxane composition, characterized in that: It includes organohydrogen polysiloxane, organopolysiloxane containing alkenyl and thermal conductive filler, wherein the thermal conductive filler includes modified alumina and unmodified alumina, wherein the modified alumina is modified by a silane coupling agent, and the unmodified alumina is not modified by a silane coupling agent; The composite mass ratio of the modified alumina to the unmodified alumina is 0.2-5.

2. An organopolysiloxane composition according to claim 1, characterized in that: The particle size D50 of the modified alumina is 2-5 μm, and the particle size D50 of the unmodified alumina is 0.5-1 μm.

3. An organopolysiloxane composition according to claim 1, characterized in that: The modified alumina has a spherical structure, and the unmodified alumina has an elliptical structure.

4. The organopolysiloxane composition according to claim 1, characterized in that: The thermally conductive filler comprises the following parts by weight: 30~600 parts of modified alumina; 30~600 parts of unmodified alumina.

5. The organopolysiloxane composition according to claim 1, characterized in that: Also includes the following components in parts by weight: 100 parts of organopolysiloxane containing alkenyl groups; 10~60 parts of toughening diluent; 20-40 parts of organohydrogenpolysiloxane; 1~15 parts of tackifier; Inhibitor 0.01~5 parts; 5~30 parts of diluent.

6. An organopolysiloxane composition according to claim 5, characterized in that: The catalyst is a platinum group metal catalyst, and the content of the platinum group metal catalyst is 0.01 to 1000 ppm relative to the mass of the organopolysiloxane resin in terms of the mass of the platinum group metal; The toughening diluent is a VMD structured vinyl-terminated silicone oil, and the viscosity of the toughening diluent is 50-500cp; The tackifier comprises an organic silicon polymer containing epoxy, vinyl and methoxy groups, the content of vinyl in the tackifier is 0.05-1 mol / 100g, and the equivalent of epoxy in the tackifier is 200-600.

7. An organopolysiloxane composition according to claim 5, characterized in that: The alkenyl-containing organopolysiloxane is a vinyl VMQ type resin having a vinyl content of 0.05 to 1.1 mol / 100g; The organohydrogenpolysiloxane includes one or more hydrogen-containing compounds of HMQ and HMD structures; The viscosity of the organohydrogenpolysiloxane is 1-50 cp, and the hydrogen content of the organohydrogenpolysiloxane is 0.6-2 mol / 100g.

8. The method for preparing the organopolysiloxane composition according to any one of claims 1 to 7, characterized in that: The following operations are included: The alkenyl-containing organopolysiloxane, toughening diluent and inhibitor are uniformly mixed to obtain a resin solution; Add the thermal conductive filler to the resin solution and mix evenly to obtain a base colloid; Taking a tackifier and an organohydrogen polysiloxane and mixing them evenly to obtain a preformed colloid; The catalyst is added to the prefabricated colloid, and the organic polysiloxane composition is obtained after mixing and degassing.

9. A chip mounting material, characterized in that: The organopolysiloxane composition comprises the organopolysiloxane composition according to any one of claims 1 to 8.

10. An optical semiconductor device, characterized in that: The chip attach material comprising the chip attach material according to claim 9.